Penguatan Pengetahuan Energi Terbarukan Dan Peran Teknik Sistem Energi: Kegiatan Pengabdian Di SMA Negeri 12 Bandar Lampung - Ilham Dwi Arirohman; Khoirun Naimah; Muhammad Rizky Zen; Rihardian Maulana Wicaksono (CV. Multi Kreasi Media, 2025)
The low public awareness and understanding of renewable energy, particularly among younger generations, remains a challenge for accelerating the energy transition in Indonesia. This community service activity aimed to enhance the knowledge and awareness of students at SMA Negeri 12 Bandar Lampung regarding renewable energy, while introducing the Energy Systems Engineering Program at ITERA as part of the transition solution. The method included planning, interactive dissemination, and evaluation through pre- and post-tests. A total of 135 students participated in the activity, which utilized visual presentations and interactive quizzes (Quizziz). Evaluation results showed a significant increase in student understanding, with more than 93% showing improved post-test scores. These findings indicate that visual and interactive educational approaches are effective in improving energy literacy at the secondary education level. This activity also serves as a practical means of disseminating scientific knowledge from the Energy Systems Engineering field to the broader community.